The geography of banks in the United States (1990-2020) - Ignazio Angeloni; Johannes Kasinger; Chantawit Tantasith (Leibniz Institute for Financial Research SAFE, 2021)
We present new statistical indicators of the structure and performance of US banks from 1990 to today, geographically disaggregated at the level of individual counties. The constructed data set (20 indicators for some 3150 counties over 31 years, for a total of about 2 million data points) conveys a detailed picture of how the geography of US banking has evolved in the last three decades. We consider the data as a stepping stone to understand the role banks and banking policies may have played in mitigating, or exacerbating, the rise of poverty and inequality in certain US regions.
Keywords: 330; Bank; Räumliche Verteilung; Bankgeschichte; Bibliometrie; Statistik; USA